CHALLENGES AND CONSTRAINTS TO THE STRENGTHENING OF AN ENTREPRENEURIAL ECOSYSTEM IN THE CITY OF RIO DE JANEIRO: AN ANALYSIS BASED ON THE MAIN PLAYERS' VIEW (Gestão & Regionalidade, 2019)
The purpose of this article is studying the challenges and constraints to the strengthening of an Entrepreneurial Ecosystem in the city of Rio de Janeiro. For this purpose, firstly we did a bibliographic review about entrepreneurial ecosystems and a contextualization of the current scenario based on secondary data. Afterwards, we carried out interviews by e-mail with different actors that compose the entrepreneurial ecosystem of Rio de Janeiro. The answers were analyzed through the Content Analysis technique, based on the selected categories. The results indicate that the entrepreneurial ecosystem of Rio de Janeiro is still shortly developed, in spite of its great growth potential. The main obstacles and challenges are: the excessive bureaucracy; the limited availability of funding; the lack of articulation among the actors; the increase of the number of events for entrepreneurs and the creation of shared spaces; and a bigger incentive to impact investing.
Keywords: Ecosystem; Startups; Entrepreneurship; City of Rio de Janeiro; Innovation